Meaning configuration of cultural practices in Bali as a model to strengthen identity of Balinese people - Netra, I Made (International research journal of management, IT and social sciences, 2015)
This paper attempts to configure the meaning of cultural practices in the field of tradition in Bali including the cultural meaning of assertive, directive, expressive, commissive, and declaration that can be used as a model TO strengthen the identity of Balinese people. In order to obtain valid data, participative observation taking the form of a focused group discussion was done in several locations in Bali. The data were then thoroughly analyzed based on the theory of Natural Semantic Metalanguage originated by Wierzbicka (1999) with a model of Cultural Scripts proposed by Goddarad (2002). The result of analysis showed that: 1) cultural meanings found in verbal utterance of traditional cultural practices in Bali could be derived from such functions of speech acts as (a) assertive with cultural meanings of ngaturang 'to present and ngedengang 'to show '; (b) directive with cultural meanings of ngelungsur keslametan ‘to ask for safety', nuturang 'to advise', ngundang 'to invite'; (c) expressive with cultural meanings of ampura 'to apologize' and suksma 'to thank'; (d) commissive with cultural meaning of mejanji 'to promise'; and (e) declaration with cultural meaning of mutusang 'to decide'; 2) Cultural meanings of Bali cultural practices could be configured using cultural scripts that can be used as a model to strengthen the identity of Balinese people.